(untitled) (TAJ: Journal of Teachers Association, 2020)
Carcinoma pancreas is the fourth common cause of the death from cancer in man and women in USA. The condition becomes increasingly common over the age of 70 years. The total number of carcinoma pancreas patients available for the study within the stipulated time was 22. Among them 68.18% patients were male and 31.82% patients were female. 0% belonged to age group ≤ 20, 9.09% belonged to age group 21-30, 18.18% belonged to age group 31-40, 18.18% belonged to age group 41-50, 13.64% belonged to age group 51-60, 27.27% belonged to age group 61-70 and 13.64% patients were >70 years of age. Mean age was 54.87 years ± 17.65 SD. In our study, 46.7% survived ≤3 months, 33.3% 4-6 months, 13.3% 7-9 months, 06.7% 10-12 months, 0% 13-24 months and >24 months. Among 15 expired patients, 02 got curative treatment and rest of 13 got palliative treatment. Those who got curative treatment, 50% survived 7-9 months and 50% 10-12 months. Those who got palliative treatment 53.8% survived ≤3 months, 38.5% 4-6 months and 7.7% 7-9 months. Overall median survival was 04 months, for curative treatment was 09 months and for palliative treatment was 03 months. TAJ 2020; 33(1): 11-16